The impact of kaolin mining activities on bacterial diversity and community structure in the rhizosphere soil of three local plants - Gao, Wei; Chen, Xiaodie; He, Jing; Sha, Ajia; Ren, Yuanhang; Wu, Peng; Li, Qiang (Frontiers in Microbiology, 2024)
Thus far, the impact of kaolin mining activities on the surrounding native plants and rhizosphere microecology has not been fully understood. In this study, we used 16S rRNA high-throughput sequencing to examine the impact of kaolin mining on the rhizosphere bacterial communities and functions of three local plant species: Conyza bonariensis, Artemisia annua, and Dodonaea viscosa. The results showed that kaolin mining significantly reduced the diversity of rhizosphere bacteria in these plants, as indicated by the Shannon, Simpson, Chao1, and observed species indices (P<0.05).Kaolin mining had an impact on the recruitment of three rhizosphere bacteria native to the area: Actinoplanes, RB41, and Mycobacterium. These bacteria were found to be more abundant in the rhizosphere soil of three local plants than in bulk soil, yet the mining of kaolin caused a decrease in their abundance (P<0.05). Interestingly, Ralstonia was enriched in the rhizosphere of these plants found in kaolin mining areas, suggesting its resilience to environmental stress. Furthermore, the three plants had different dominant rhizosphere bacterial populations in kaolin mining areas, such as Nocardioides, Pseudarthrobacter, and Sphingomonas, likely due to the unique microecology of the plant rhizosphere. Kaolin mining activities also caused a shift in the functional diversity of rhizosphere bacteria in the three local plants, with each plant displaying different functions to cope with kaolin mining-induced stress, such as increased abundance of the GlpM family and glucan-binding domain. This study is the first to investigate the effects of kaolin mining on the rhizosphere microecology of local plants, thus contributing to the establishment of soil microecological health monitoring indicators to better control soil pollution in kaolin mining areas.